Accio nell'età degli Antonini: il giudizio di Frontone - Fabi, Alessandro (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
This paper aims to analyze the reception of Accius in Fronto’s Epistulae. The connections between Accius and Fronto emphasize various interesting aspects (e.g. Fronto’s influences on the emperors’ literary background); simultaneously, they point up some questions which might seem to require caution: in contrast with some previous authors, Fronto’s value judgement does not seem particularly enthusiastic; moreover, Accius seems to be part of a canon. Finally, Van den Hout’s editions show the persistence of some textual problems, with the result that testimonia appear uncertain and need to be discussed.